Striving for Discussion: An Analysis of a Teacher Educator's Comments in Whole-Class Conversation. Issue 2 (3rd May 2016) - Reynolds, Todd
Abstract: During my English Language Arts methods class, I noticed that my discussion patterns were teacher-focused and in an Initiation-Response-Evaluation format. Because I wanted to model dialogic methods of whole-class discussions for my preservice teachers, I recoiled from this finding and began a self-study using an action research method to examine the techniques and comments I used while leading whole-class discussion. Using dialogic instruction as the theoretical perspective, I examined 11 class sessions, including 32 whole-class discussion events. I found that I was using phrases that stopped student-to-student interaction and that I often took over the conversations. These findings led to more questions about the nuance in the analysis of whole-class discussion, as well as some specific concepts that I incorporated into my teaching of the next year's class.